Sextarianism: sovereignty, secularism, and the state in Lebanon - Mikdashi, Maya (Stanford University Press, 2022)
Afterlives of a census : rethinking state power and political difference from Lebanon -- A fire in the archive : history, ethnography, multiplicity -- Regulating conversion : sovereignty, bureaucracy, and the banality of religion -- Are you going to pride? : evangelical secularism and the politics of law -- The epidermal state : violence, sovereignty and the materiality of power.